The effect of ethanol sclerotherapy of 5 minutes duration on cyst diameter and rat ovarian tissue in simple ovarian cysts - Simsek, Mehmet; Kuloglu, Tuncay; Pala, Sehmus; Boztosun, Abdullah; Can, Behzat; Atilgan, Remzi (Dove Medical Press Ltd, 2015)
Objectives: To examine the effect of 95% ethanol sclerotherapy (EST) administered over 5 minutes on cyst diameter and ovarian tissue in experimentally induced simple ovarian cysts in a rat model. Materials and methods: In order to induce ovarian cysts, unilateral total salpingectomy was performed in regularly menstruating adult female Wistar albino rats (n=20) between 12 and 14 weeks of age and weighing between 200 and 220 g. One month after the procedure, the abdominal cavity was opened and 14 rats (70%) were found to have developed macroscopic cysts. Rats with macroscopic cysts (n=14) were assigned into two groups in a prospective and single-blinded manner: group 1 (G1) (n=7), control rats; and group 2 (G2) (n=7), 5-minute EST 95% group. Cyst diameter was measured and recorded for each rat. In G2, after whole cyst fluid was aspirated the cystic cavity was irrigated with 95% ethanol, approximately equal to half of the aspirated cyst volume, after which an interval of 5 minutes was allowed and same amount was re-aspirated and the abdominal cavity was closed. One month after this procedure, abdominal cavities were reopened and intra-abdominal adhesion scoring was performed in both groups. Cyst diameter was measured for each rat, and the right ovary was removed, fixed in 10% formaldehyde, and transported to the laboratory. A histologic assessment of the ovarian tissues was performed under light microscopy following staining with hematoxylin and eosin. Mann-Whitney U-test was used for statistical analysis. A P-level less than 0.05 was considered significant. Results: In comparison with G1, there was a statistically significant reduction in the mean ovarian cyst dimensions in G2, while there were no significant differences between the two groups with respect to total number of follicles. Again, a significant increase in apoptotic activity and germinal epithelial degeneration was observed in G2 as compared to G1. The two groups were similar in terms of adhesion formation. Conclusion: Although 95% EST results in a reduction in the size of simple ovarian cysts, this effect seems to be achieved at the expense of ovarian tissue injury.
Keywords: ethanol instillation; salpingectomy; ovarian morphology; simple ovarian cyst; adhesion